2007
DOI: 10.4103/0019-5413.33685
|View full text |Cite
|
Sign up to set email alerts
|

Internal fixation of fractures of the shaft of the humerus by dynamic compression plate or intramedullary nail: A prospective study

Abstract: Background:The indications for surgical management of fractures of the shaft of the humerus are clear, but selecting the right implant for internal fixation of humeral fractures has been a dilemma.Materials and Methods:Thirty-six patients (mean age 40.53 years) with fractures of the shaft of the humerus were followed for 12 to 24 months in a prospective study. Eighteen patients each underwent open reduction and internal fixation with compression plating and ante grade interlock nailing. Clinical and radiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
45
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 27 publications
3
45
3
2
Order By: Relevance
“…The higher rate of excellent and good results with the plating group patients seen in our series was also cited in many other reports [13,15]. But another series has suggested that both groups had predictable results and neither of them is markedly superior [7].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The higher rate of excellent and good results with the plating group patients seen in our series was also cited in many other reports [13,15]. But another series has suggested that both groups had predictable results and neither of them is markedly superior [7].…”
Section: Discussionsupporting
confidence: 63%
“…Impairment of shoulder function with the antegrade interlocking nails could be because of impingement due to proximal migration of nail, rotator cuff violation, adhesive capsulitis or due to an unexplained cause [6,7,15,17]. This problem can be potentially minimised by using a retrograde technique but carries a risk of elbow movement restriction and fracture at the insertion point [4,9,15]. Some report increased incidence of elbow stiffness with the plating group [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] Shoulder pain and restriction of shoulder movements and risk of delayed union have been suggested as disadvantages of antegrade intramedullary fixation. [18][19][20] Impairment of shoulder function with antegrade IMN could be due to rotator cuff violation, and subacromial impingement. Baltov et al in their retrospective review of 105 patients treated with antegrade approach reported telescopic effect in 5 (4.5%) patients with osteoporosis, incomplete embedding of the nail at surgery, leading to sub acromial impingement in 12 (10.8%) cases, and in 5 (4.5%) patients impingement of the head of proximal interlocking screw as complications leading to shoulder discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Однією з найважливiших умов для зрощення переломiв є механічна стабільність уламків та малоiнвазивність з урахуванням опосеред-кованого пошкодження м'яких тканин, що суттєво впливає на процеси репаративної регенерацiї [4,6,10]. Також використання блокуючого iнтрамедулярного остеосинтезу (БІОС) надає можливiстъ забезпечен-ня раннього навантаження на оперовану кiнцiвку при мiнiмальному ризику виникнення нестабільності кісткових уламків чи імпланта та вiдновлення функції травмованої кінцівки в мiнiмальнi термiни [3,7,8].Мета дослiдження -оцiнити ефективнiсть вико-ристання методу блокуючого iнтрамедулярного остео-синтезу для лiкування постраждалих з діафізарними переломами плечової кістки. …”
unclassified